Disposition of Students Learning Independence to Support Learning Success During the COVID-19 Pandemic - Yayan Eryk Setiawan; Ahmad Sufyan Zauri; Rr. Ettie Rukmigarsari; Syaifuddin Syaifuddin; Yuli Ismi Nahdiyati Ilmi (Universitas Pendidikan Ganesha, 2022)
Nowadays online learning causes a decrease in student understanding. One of the factors that influence this decrease is the student's thinking disposition. Thus, it is important to identify the dispositions needed by students to support their success in online learning. The purpose of this study was to identify the disposition of learning independence that is used as a supporter of successful online learning. The method of this research is quantitative research with a survey approach. The sample of this study consisted of 138 students in the mathematics education study program. The data collected in this study are the results of filling out questionnaires and student opinions related to thinking dispositions. The survey results show that there are four components of thinking disposition that are needed by students to be successful in online learning, namely: persistence, motivation, communication, and self-regulation. These four components are interrelated with each other. Someone successful in learning must have persistence, where persistence is built from motivation. Someone persistent and motivated must also be able to communicate with various parties. Persistence, motivation, and communication must pay attention to self-regulation. These four components of thinking disposition can be used to support student success.